PENGARUH PENAMBAHAN POTONGAN KARET BAN TERHADAP KUAT TARIK BELAH BETON - Ramadhan, Muhammad Rehan; Firdaus, Firdaus (Ensiklopedia of Journal, 2024)
This research aims to determine the results of the effect of adding pieces of tire rubber on the split tensile strength of concrete. This research was conducted at the Civil Engineering Laboratory, Campus C, Bina Darma University. The object used in this research is the effect of adding pieces of tire rubber on the split tensile strength of concrete with percentages of 5%, 10% and 15%. The results of research and analysis regarding the influence of adding pieces of tire rubber on the splitting tensile strength of concrete in the form of small pieces measuring 2 cm long and 2 mm wide have a very positive impact on the splitting tensile value of concrete, this is in line with the increase in the splitting tensile strength value in each percentage of test objects such as normal concrete 7 days, 21 days and 28 days has an average split tensile strength value of 2.41 Mpa 2.61 Mpa and 3.03 Mpa, the percentage of 5% aged 7 days, 21 days and 28 days has a value The average splitting tensile strength is 2.51 Mpa, 2.75 Mpa and 3.03 Mpa and 15% aged 7 days, 21 days and 28 days have an average splitting tensile strength value of 2.63 Mpa, 2.85 Mpa and 3.19 Mpa, meaning that there is an increase in the splitting tensile strength value of normal concrete by 3.19 Mpa. So this piece of tire rubber has a positive effect and is suitable as an alternative addition to modified concrete mix, and is suitable for use in cylinders in residential buildings, house foundations and bridges.Keywords: Concrete, Split Tensile Strength, Tire Rubber